Governance of Islamic Banks in Palestine - Rajoub, Salim (Jordan Journal of Islamic Studies, 2023)
The purpose of this study is to clarify the meaning of the governance of Islamic banks in Palestine, and the extent of their effectiveness in achieving transparency and stability of economy. It consists of two parts: the first one explains the meaning of governance in general, the circumstances of its inception, its purposes, and elements. The second one focuses on governance in Islamic banks as an organizational management work aimed at raising the level of performance of Islamic banks and thus increasing confidence by investors, shareholders and the general public. The study concluded that the system of governance that has been created as a result of certain economic conditions in the world fits in accordance with the Islamic Shari’a and is considered within the framework of the interests which are reasonable, and its benefit is clear. Moroever, the Shari’a is concerned with the interests of the people.